Rapid Diagnosis of Soya Bean Root Rot Caused by Fusarium culmorum Using a Loop‐Mediated Isothermal Amplification Assay. Issue 4 (April 2017) - Zeng, Dandan; Ye, Wenwu; Xu, Miao; Lu, Chenchen; Tian, Qing; Zheng, Xiaobo
Abstract: We report a rapid diagnosis of soya bean ( Glycine max L.) root rot caused by Fusarium culmorum, using a loop‐mediated isothermal amplification (LAMP) assay. We used the CYP51C gene sequence to design LAMP assay primers specific for F. culmorum . The LAMP assay amplified the target gene efficiently in 60 min at 63°C. The sensitivity of the assay was 100 pg/ μ l of genomic DNA. Among the tested soya bean pathogens, a positive colour (sky blue) was only observed in the presence of F. culmorum with the addition of hydroxynaphthol blue (HNB) dye prior to amplification, whereas other species isolates showed no colour change. Suspected diseased soya bean samples collected in the field from Jiangsu, Shandong and Anhui provinces and Beijing were diagnosed successfully using the LAMP assay reported here. This study provides a new and readily available method for rapid diagnosis of soya bean root rot caused by F. culmorum .